Usability analysis of graphic user interfaces for Internet forums with consideration for Universal Design Principles - Łęczycki, Krystian; Łabendowicz, Jakub; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2025)
Universal design is about creating applications to be accessible to a wider range of users. The paper presents the methodology and results of study on user interfaces of online forums. The main aim of the study is to conduct a comparative analysis of two internet forums. For the purposes of the study, the following research hypothesis was defined: "The application of universal design principles (UDP) increases the accessibility of online forums". In order to conduct the study, the "Elektroda" Internet forum was selected, which does not apply the principles of universal design. Additionally, the authors own Internet forum has been created to meet the universal design principles. An experiment was designed consisting of an eye-tracking tool, the LUT (Lublin University of Technology) and the SUS (System Usability Scale) surveys. 22 participants, students of master’s studies in computer science at the Lublin University of Technology, were involved in this study. An evaluation of two web services has also been carried out using the WAVE (Web Accessibility Evaluation) tool. The results of the conducted research confirmed the hypothesis, showing that the application of universal design principles increases the accessibility of online forums.